Gut Bacteria Metabolism Impacts Immune Recovery in HIV-infected Individuals - Sergio Serrano-Villar; David Rojo; Mónica Martínez-Martínez; Simon Deusch; Jorge F. Vázquez-Castellanos; Rafael Bargiela; Talía Sainz; Mar Vera; Santiago Moreno; Vicente Estrada; María José Gosalbes; Amparo Latorre; et al. (EBioMedicine, 2016)
While changes in gut microbial populations have been described in human immuno-deficiency virus (HIV)-infected patients undergoing antiretroviral therapy (ART), the mechanisms underlying the contributions of gut bacteria and their molecular agents (metabolites and proteins) to immune recovery remain unexplored. To study this, we examined the active fraction of the gut microbiome, through examining protein synthesis and accumulation of metabolites inside gut bacteria and in the bloodstream, in 8 healthy controls and 29 HIV-infected individuals (6 being longitudinally studied). We found that HIV infection is associated to dramatic changes in the active set of gut bacteria simultaneously altering the metabolic outcomes. Effects were accentuated among immunological ART responders, regardless diet, subject characteristics, clinical variables other than immune recovery, the duration and type of ART and sexual preferences. The effect was found at quantitative levels of several molecular agents and active bacteria which were herein identified and whose abundance correlated with HIV immune pathogenesis markers. Although, we cannot rule out the possibility that some changes are partially a random consequence of the disease status, our data suggest that most likely reduced inflammation and immune recovery is a joint solution orchestrated by both the active fraction of the gut microbiota and the host.